Impacto do cuidado farmacêutico em unidades de terapia intensiva de ambiente materno-infantil: uma revisão sistemática de estudos primários - Silva, Ítalo Assis Bezerra da (2022)
The pharmacist, through the Clinical Pharmaceutical Services (SCF), assumes an important role in the promotion and recovery of patients' health by acting in the optimization of pharmacotherapy. In this sense, the systematic review evaluated the clinical, process, and economic outcomes generated from the pharmaceutical intervention, in patients from maternal-pediatric intensive care units (ICU). Recommendations of the PRISMA declaration and COCHRANE collaboration were followed, respecting all phases, and being carried out by two independent reviewers. After screening and eligibility, 8 primary studies (2 cohorts, 4 cross-sectional and 2 community trials) were included, totaling a population of approximately 1,400 patients. The quality of the included studies ranged from low to high risk of bias according to the Newcastle-Ottawa Scale (NOS) for cohort and cross-sectional studies, and from moderate to severe risk of bias, according to the Risk Of Bias In Non-randomized Studies - of Interventions (ROBINS-I) for non-randomized interventional studies. The results showed that the interventions of the clinical pharmacist have the potential to reduce drug-related problems (DRP) and medication errors (ME) in critically ill patients in the maternal and child environment, besides having a possible influence on cost reduction for a hospital institution. Thus, this study evidences that the clinical pharmacist has a positive impact on the clinical, process, and economic outcomes of patients in intensive care.